Quand des pesticides empoisonnent la recherche, la réglementation et la démocratie : - Louise Vandelac (VertigO)
Never in the history of science has been published such a detailed account of the attacks and perfidious manipulations of an agribusiness giant to destroy the reputation and life of one of the most published scientists on its flagship product : Bayer-Monsanto's Roundup, the world's best-selling pesticide and a glyphosate-based herbicide used on GMOs designed to absorb it without dying, a key to agro-industrial concentration. Gilles-Éric Seralini, a molecular biologist and university professor, subject of these persecutions which led him to file seven defamation lawsuits - all won - could have never suspected the scope and severity of these attacks whose main strings are revealed in this exceptional investigative account. Indeed, this analytical work, based on Seralini's first-hand experience and on, something utterly unique, 2.5 million pages of internal documents from Bayer-Monsanto, the Monsanto Papers, declassified during the first American trials against Bayer-Monsanto of the 125.000 victims of non-Hodgkin lymphoma (NHL), attributed to Roundup, and on the 20.000 pages where Seralini's name appears 55.952 times. Thus, for discerning the company's dubious schemes too clearly, he became its target. Without losing sight of the essential points, Seralini and Douzelet expose the agrochemical giant’s tremendous power to manipulate information to conceal Roundup’s toxicity, but above all, the extent of its strategies to subvert the very foundations of public regulations intended to protect health and the environment. As a result, it is the regulation of all pesticides that is targeted, with its huge economical stakes, but more significantly, a vital one for health, food, and biodiversity. To oppose opacity and lies, they therefore shed light on the Monsanto Papers (U.S. Right to Know [online] URL : https://usrtk.org/), provide access to scientific articles [online] URL : www.seralini.fr, and expose the landmarks of this saga in a recent seminar [online] URL : https://www.unicaen.fr/recherche/mrsh/forge/6930.